2023
DOI: 10.3389/fmicb.2023.1165131
|View full text |Cite
|
Sign up to set email alerts
|

Dark septate endophyte Exophiala pisciphila promotes maize growth and alleviates cadmium toxicity

Abstract: Dark septate endophytes (DSE) are typical root endophytes with the ability to enhance plant growth and tolerance to heavy metals, but the underlying mechanisms are unclear. Here, the physiological and molecular mechanisms of a DSE strain, Exophiala pisciphila, in mitigating cadmium (Cd, 20 mg/kg) toxicity in maize were investigated. Our results showed, under Cd stress, E. pisciphila inoculation enhanced the biomass of maize and reduced both inorganic and soluble forms of Cd (high toxicity) by 52.6% in maize le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 68 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Similarly, DSE colonization in roots resulted in a significant decrease in ABA levels in soybean (Glycine max L.) under Cu stress (Khan and Lee et al, 2013), and a decrease in ABA levels and an increase in GA levels in cucumber (Cucumis sativus L.) under salt stress, thereby stimulating the growth of plant roots, improving nutrient absorption, and promoting plant growth (Khan et al, 2012;Sukumar et al, 2013). The DSE significantly affected the gene expression involved in phytohormone transport and the ABA and IAA contents in maize roots, which was considered as the main reason for promoting maize growth (Wang et al, 2023). Similarly, faba beans inoculated with endophytic fungi (Aspergillus niger and Penicillium chrysosporium) promoted plant growth and nutrient uptake by regulating endogenous plant hormones under Pb stress (El-Mahdy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, DSE colonization in roots resulted in a significant decrease in ABA levels in soybean (Glycine max L.) under Cu stress (Khan and Lee et al, 2013), and a decrease in ABA levels and an increase in GA levels in cucumber (Cucumis sativus L.) under salt stress, thereby stimulating the growth of plant roots, improving nutrient absorption, and promoting plant growth (Khan et al, 2012;Sukumar et al, 2013). The DSE significantly affected the gene expression involved in phytohormone transport and the ABA and IAA contents in maize roots, which was considered as the main reason for promoting maize growth (Wang et al, 2023). Similarly, faba beans inoculated with endophytic fungi (Aspergillus niger and Penicillium chrysosporium) promoted plant growth and nutrient uptake by regulating endogenous plant hormones under Pb stress (El-Mahdy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The glutathione (GSH) content was determined using the method described in the GSH test kit produced by Nanjing Jiancheng Bioengineering Institute, according to previous methods (Wang et al, 2023). The supernatant obtained by centrifugation was used for the determination of the GSH content by measuring the absorbance at 405 nm.…”
Section: Determination Of Glutathione Metabolism In Maize Rootsmentioning
confidence: 99%
“…Functional predictions further confirmed that Exophiala and Didymellaceae are core species playing an important role in coralloid roots ( Figure 6 ), thus solidifying their status as essential members of the coralloid root microbiome. A recent study demonstrated that symbiotic Exophiala can promote maize growth by regulating the expression of genes involved in plant hormone signaling and polar transport in maize roots, which affected abscisic acid (ABA) and indole-3-acetic acid (IAA) contents [ 75 ]. The abundance of Exophiala from the biological soil crusts was found to have a positive correlation with microbial biomass nitrogen (MBN), electrolytic conductivity (EC), nitrate (NO 3 − ), suggesting its potential for nitrogen fixation [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Symbiosis between plants and microorganisms occurs wide in natural ecosystems, affects plant terrestrializations (Puginier et al, 2022), evolution (Batstone, 2022;van Galen et al, 2023), and tolerance to abiotic and biotic stress (Zeng et al, 2022), and widens the habitability ranges of plants (Muñoz and Carneiro, 2022). Among all the beneficial microorganisms symbiosing with plants, five families of microorganisms have been greatly paid on attentions, i.e., arbuscular mycorrhizal fungi (Kaur et al, 2022;Razak and Gange, 2023;Chen W. et al, 2023), ectomycorrhizal fungi (Karlsen-Ayala et al, 2022;Jörgensen et al, 2023;Xiao et al, 2023), root endophytic fungi (Manzur et al, 2022;Sun et al, 2022;Qin et al, 2023), dark septate fungi (Gaber et al, 2023;Wang et al, 2023;Chen S. et al, 2023), and plant growth-promoting rhizobacteria (PGPR) (Ahmad et al, 2022;Gowtham et al, 2022;Zhao et al, 2023). These beneficial microorganisms show strong effects on their plant hosts under drought stress (Ahmad et al, 2022;Gowtham et al, 2022;Zhao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%